Nutrient fluxes within the Berg River from 1976 to 2017, Western Cape, South Africa - Molebatsi, Lemogang (Department of Environmental and Geographical Science, 2020)
Deterioration of freshwater systems due to eutrophication is increasingly a global concern because it puts stress on the already limited freshwater systems. Eutrophication is caused by elevated levels of nutrients in river systems primarily from poor land management whereby excess nutrients are discharged into fresh water bodies. It is exacerbated by factors such as human population growth, economic growth and climate change. The main aim of this study was to analyze the changes in the nutrient status of the Berg River since the 1970s and tendencies toward hypertrophic conditions. The Berg River is an important source of bulk water supply for both domestic and industrial purposes in the Western Province, South Africa. The study examined water quality data from the Department of Water and Sanitation’s Resource Quality Information Services for nine monitoring sites along the Berg River to determine the long-term trends. The data sets were analyzed using parametric statistics. The results show that nutrient levels in the Berg River are increasing at almost all the selected monitoring sites. The long term trend showed low mean values for both upstream and downstream with a peak nutrient levels observed along sections that were densely populated and extensively cultivated. Based on available total phosphorus data, all sites were classified as eutrophic except a monitoring site along the most populated and cultivated section of the Berg River which was permanently hypertrophic. Long-term mean values for total phosphorus exceed the recommended international guidelines for aquatic plant life. The long-term mean values of nitrate and nitrite also exceed the recommended guideline for aquatic plant life. Ortho-phospate mean values for the study showed that all sites experienced hypertrophic states at some stage during 1987 to 2017. Student t-test analyses confirm that nutrient concentration loads had increased in the past decade. The results confirm that anthrophogenic activities and climate change are two major drivers of change resulting in an increase in eutrophication. Therefore, serious attention should be paid to the role of anthrophogenic activites and climate change to mitigate the negative impact on freshwater systems.